PREVALENCE OF PERI-IMPLANT DISEASE AROUND SUBCRESTAL PLACED IMPLANTS - Alper Sağlanmak; Volkan Arısan (Sabiad)
Objective: To investigate the long-term peri-implant health of subcrestal placed implants and identify the local factors influencing it. Material and Methods: A total of 103 patients participated in this crosssectional study. Subcrestal placed implants (n=322) were followed up. Patients were assessed for peri-implant health status at routine visits and the results were recorded. Binary logistic regression analysis was used to investigate factors influencing the peri-implant health status. Results: The peri-implant health of 103 patients was analysed. The mean function time was 14.05±5.95 years. In total, 47.5% of the patients were found to be healthy. 31% had peri-implant mucositis and 21.5% had periimplantitis. When all variables were analysed, it was found that periimplant mucositis and peri-implantitis were significantly associated with the following outcomes: additional instruments adjunct regular brushing [Odds ratio (OR):11.23]; and type of prosthesis retention [Odds ratio (OR):4.032]. Conclusion: Peri-implant mucositis and peri-implantitis occur in approximately half of subcrestal placed implants, and the use of oral hygiene instruments in addition to regular brushing and screw-retained prostheses plays an important role in implant survival.